2015
DOI: 10.4236/ss.2015.66037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Intraoperative Application of a Haemostatic Agent (PerClot<sup>&reg</sup>) with Conventional Haemostatic Procedure after Thyroid Resection

Abstract: Background: Postoperative hemorrhage remains an uncommon but potentially life-threatening complication of thyroid surgery. The aim of this case-controlled study was to compare the effectiveness of PerClot ® hemostatic agent with hemostasis by conventional technique (HCT) in thyroid surgery. Methods: The thyroid resection was performed from November 2009 to February 2010. Exclusion criteria were applied. There were 30 patients in the HCT group and 30 patients in the PerClot ® group. The outcome parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There have been various studies that have published regarding the safety and effectiveness of haemostatic agents in operations in head and neck and we know only one that relates to the use of PerClot ® , the study conducted by Thomas von Ahnen et al [5] The ideal haemostatic agent should be inexpensive, bioabsorbable, effective, safe and easy to use. On reviewing the literature, there is some evidence of adverse events reported for haemostatic agents such as wound infection, allergic reactions, nerve entrapment [10] and can cause misleading postoperative imaging interpretation [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been various studies that have published regarding the safety and effectiveness of haemostatic agents in operations in head and neck and we know only one that relates to the use of PerClot ® , the study conducted by Thomas von Ahnen et al [5] The ideal haemostatic agent should be inexpensive, bioabsorbable, effective, safe and easy to use. On reviewing the literature, there is some evidence of adverse events reported for haemostatic agents such as wound infection, allergic reactions, nerve entrapment [10] and can cause misleading postoperative imaging interpretation [11].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome parameters were postoperative bleeding, the drainage volume 24 h postoperatively and adverse events. This study concluded that PerClot ® had no advantage over conventional hemostasis technique in thyroid surgery, while reported to be safe and well tolerated [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations